INTEGRATION OF PHYSICS AND CHEMISTRY IN TEACHING DALTON’S AND AVOGADRO‘S LAWS (Universal International Scientific Journal, 2026)
This article discusses the significance of integrating physics and chemistry in teachingDalton’s and Avogadro‘s laws. The physical and chemical essence of these gas laws is elucidated, andthe effectiveness of using interdisciplinary connections to explain them to students is substantiated. Thepaper also highlights how an integrated approach can foster students’ scientific thinking and logicalreasoning skills.
Keywords: Avogadro‘s law; interdisciplinary integration; Dalton’s law